Problem of the Week

Updated at Aug 19, 2019 8:16 AM

For this week we've brought you this equation problem.

How would you solve the equation \(\frac{{(p-3)}^{2}+2}{3}=\frac{2}{3}\)?

Here are the steps:



\[\frac{{(p-3)}^{2}+2}{3}=\frac{2}{3}\]

1
Multiply both sides by \(3\).
\[{(p-3)}^{2}+2=\frac{2}{3}\times 3\]

2
Simplify \(\frac{2}{3}\times 3\) to \(\frac{6}{3}\).
\[{(p-3)}^{2}+2=\frac{6}{3}\]

3
Simplify \(\frac{6}{3}\) to \(2\).
\[{(p-3)}^{2}+2=2\]

4
Cancel \(2\) on both sides.
\[{(p-3)}^{2}=0\]

5
Take the square root of both sides.
\[p-3=0\]

6
Add \(3\) to both sides.
\[p=3\]

Done